PEMBERDAYAAN SANTRI UPAYA OPTIMALISASI RUANG TERBUKA HIJAU DAN PENATAAN LANDSCAPE DI PONPES EL-YASMIN - Bunyamin Bunyamin; Siti Munfariqoh; Muslichah Muslichah; Sonhaji Sonhaji; Moh. Syadeli; Anang Amir Kusnanto; Sunarto Sunarto; Uke Prajoga; Djoko Sugiono; Siwi Dyah Ratnasari; Lidia Andiani (Jurnal Abdi Masyarakat, 2021)
The increasingly narrow land in urban areas makes people have to take advantage of the existing land. The concept of urban farming provides a solution by creating green open land in the midst of dense urban buildings. Empowerment of students is a positive effort to realize the goal of Islamic boarding schools to equip students with religious knowledge and general knowledge.The objectives of this activity are: 1) To increase the knowledge and skills of the students in farming on limited land. 2) Provide knowledge about urban farming that can foster an entrepreneurial spirit in the students. 3) Creating a new source of income for the cottage at least from the results of urban farming that can be consumed by the residents of the Islamic boarding school so that they can save on shopping expenses. 4) Empowering productive economic activities in Islamic boarding schools.The implementation method is carried out through training for students, coaches and teachers at Ponpes El Yasmin Banjararum, Singosari, Malang. The result of this activity is to increase the knowledge of the students to learn to live independently, foster an entrepreneurial spirit and fulfill the needs of vegetables independently.